2017
DOI: 10.1016/j.bbrc.2017.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of KRas4b with anionic membranes: A special role for PIP 2

Abstract: KRas4b is a small G-protein whose constitutively active oncogenic mutants are present in 90% of pancreatic cancers. Using fully post-translationally modified KRAS4b, we investigated the role of lipid identity in the recruitment of KRas4b to a membrane surface of defined composition. Application of a newly developed single frequency fluorescence anisotropy decay experiment to this system revealed that KRas4b has a significant binding preference for Nanodisc bilayers containing PIP2. We conducted molecular dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 25 publications
9
69
1
Order By: Relevance
“…This result directly links internal conformational fluctuation to membrane reorientation. We would like to emphasize that, although the different orientations are sampled spontaneously, they may be stabilized by protein-lipid electrostatic interactions as suggested by several previous reports (16,18,23). That intrinsic flexibility underlies the membrane orientation dynamics of G12V-KRAS is further confirmed by performing another 20 ms MD simulation using the CHARMM36 force field (24).…”
Section: G12v-kras Adopts Three Distinct Orientations With Respect Tosupporting
confidence: 68%
“…This result directly links internal conformational fluctuation to membrane reorientation. We would like to emphasize that, although the different orientations are sampled spontaneously, they may be stabilized by protein-lipid electrostatic interactions as suggested by several previous reports (16,18,23). That intrinsic flexibility underlies the membrane orientation dynamics of G12V-KRAS is further confirmed by performing another 20 ms MD simulation using the CHARMM36 force field (24).…”
Section: G12v-kras Adopts Three Distinct Orientations With Respect Tosupporting
confidence: 68%
“…The results show that the two orientations have remained stable over the course of each of the trajectories. It should be noted that for our previous K-Ras4A [Li et al, 2017] and K-Ras4B [Gregory et al, 2017] simulations with PIP2, primarily the OS1 state was found to be populated (similar to O3 in Li et al, 2017). The OS2 started simulation may not be able to interconvert to OS1 on the timescale of the current simulations, also having been stabilized by PIP2 contacts; such transition was seen, however, by Gregory et al using a membrane model with increased fluidity.…”
Section: K-ras4b On Pi(45)p2 Membrane -Interface and Orientations Stcontrasting
confidence: 51%
“…It should be noted that for our previous K-Ras4A (42) and K-Ras4B (40) simulations with PIP2, primarily the OS1 state was found to be populated (similar to O3 in Li and Buck (42)). The OS2 started simulation may not be able to interconvert to OS1 on the timescale of the current simulations, also having been stabilized by PIP2 contacts; such transition was seen, however, by Gregory et al (43) using a membrane model with increased fluidity.…”
Section: K-ras4b On Pi(45)p2 Membrane-interface and Orientations Stumentioning
confidence: 65%
“…G-domain orientation) and dynamics at the membrane. For example, recent computational investigations suggested the participation of the K-Ras.G12V G-domain in binding with POPS membrane (39 -42) and with PIP2 containing membranes (42,43). Experimental work by Ikura and colleagues (44) also provided evidence that the K-Ras G-domain exists in several distinct orientations when contacting a bilayer of POPS lipid membrane.…”
mentioning
confidence: 99%